2014
DOI: 10.1108/dpm-04-2013-0070
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual management: a neglected aspect of hygiene interventions

Abstract: Effective menstrual management is essential for the mental and physical well being of women. However, many women in low income countries lack access to the materials and facilities required. They are thus restricted in their activities whilst menstruating thus compromising their education, income, and domestic responsibilities. This study describes the menstrual management challenges faced by women in an emergency situation in Uganda. Fifty interviews and focus group discussions were conducted with women from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 20 publications
3
78
0
Order By: Relevance
“…Humanitarian crises exacerbate menstrual management challenges, given girls' and women's frequent lack of access to basic materials and disposal (International Federation of Red Cross (IFRC) 2013; Kågesten et al 2017). They must manage menstruation in overcrowded camps and informal settlements, which often lack private and safe toilets and sanitation facilities (especially at night) for changing and for washing materials (Kågesten et al 2017;Parker et al 2014;Schmitt et al 2017;Sommer 2012). The disposal of menstrual waste (Parker et al 2014) is often strongly influenced by cultural beliefs and societal taboos around menstrual blood and a need for discretion.…”
Section: Introductionmentioning
confidence: 99%
“…Humanitarian crises exacerbate menstrual management challenges, given girls' and women's frequent lack of access to basic materials and disposal (International Federation of Red Cross (IFRC) 2013; Kågesten et al 2017). They must manage menstruation in overcrowded camps and informal settlements, which often lack private and safe toilets and sanitation facilities (especially at night) for changing and for washing materials (Kågesten et al 2017;Parker et al 2014;Schmitt et al 2017;Sommer 2012). The disposal of menstrual waste (Parker et al 2014) is often strongly influenced by cultural beliefs and societal taboos around menstrual blood and a need for discretion.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1980 and2013, 12,102 outbreaks of 215 human infectious diseases, including greater than 44 million cases, were reported into the Global Infectious Disease and Epidemiology Online Network from 219 nations (Smith et al 2014). The total number of outbreaks and the diversity of causal diseases (the number of diseases causing outbreaks) have both increased over time (p<0.0001).…”
Section: Increasing Needsmentioning
confidence: 96%
“…This review is timely and important as the number of people affected by emergencies is increasing (Smith et al 2014, UNHCR 2015, EM-DAT 2014 and is anticipated to continue to increase with climate change and a rapidly growing population . Better understanding of the efficacy and effectiveness of WASH interventions in emergencies can shape how WASH interventions are implemented to better serve their target communities (Cairncross et al 2013).…”
Section: Why Is It Important To Do This Reviewmentioning
confidence: 99%
“…Some other female students still go to school and they do not change their pads until the end of their school period. Therefore, water availability inside the toilet/ bathroom is very important for cleansing hands and taking bath (Parker, 2014). A study by Shanbhag (2012) reported that there were several female students who never cleansed their genital area after they had done their urination.…”
Section: The Influence Of Family Support Toward Behaviors In the Treamentioning
confidence: 99%